Estresores psicosociales, trastornos mentales y propuesta de programa preventivo de salud mental para estudiantes universitarios - Vicuña Pérez, Hugo Alfredo (2005)
In the present study, the presence and severity of psycho-social and mental disorders in university students were investigated having as a goal the establishment of a Mental Health Prevention Program. For this purpose, a personal interview was carried out by specialized professionals using a, previously validated, semi-structured psychiatric instrument of evaluation in a representative sample of 330 students. They had been systematically selected through proportional allocation from the total of students who had passed the entrance examination for the twelve faculties of the National University of Trujillo – Peru in the year 2003. According to the results, the psycho-social stressors (economic and health problems, academic factors, hostile relations among parents and other family members, etc) were affecting the students. Besides, it was verified that in 33,9% (112 out of 330) the severity rate was high, predominating in female students. Mental disorders in activity were not identified. With the results stated above, a Mental Health Prevention Program was created and established for the students in the above-mentioned university, to be applied by the respective authorities.